The development of solar power boat engine - Mohd Hafizuddin, Mohd Ally Hussain (2010)
With the increased of fuel energy demand and fear of depletion of the fossil fuel for year ahead makes most of boat user facing problem with burdened by higher cost of the fuel. Renewable energy has remarkably the only best solution for this problem. Hence, these projects proposed to solve the problem by replacing the fuel energy with the renewable solar power energy. The proposed of the solar power boat which will be consists of the solar panel (photovoltaic cell) as sunlight collector that act as the power generator that will be supported by the battery as storage power for the boat and the load which is dc motor that replace fuel engine. The charging process will be control by the solar charger controller that uses PWM operation method. Overall system will start by the sunlight converted to the electricity and then the generated power will be transferred to the battery. Then only that the load (dc motor) can be operated. Both of these charging and running the load will be operate together. With this solar power technology, we can reduce fuel usage. Moreover, these method helps reduce air pollution that produced by the fuel engine